Future vision for development of handicraft knitting to meet the needs of contemporary society - Rawia Abdel Baqi (Journal of Architecture, Art & Humanistic Science, 2018)
None of us know the beginnings of the traditional handicrafts that the needs of the communities have called for. It has become one of the constants of our ancient heritage and the treasures of its people that cannot be removed from memory no matter how many years have passed. He derived from high technique and skills that made him an art that remained alive throughout the ages. The traditional industry is one of the main pillars that underpinned the economic environment of thousands of families, despite the decline of most of the artisans and diminishing at the present time, the most prominent of which are crafts, gold jewelry, silver jewelry, wood industry, carpets, It is worth mentioning that the handicraft of hand weaving has received a lot of turnout and spread, and we find that hand knitting craft, which can be known as Crochet in some cases can be produced in different types to meet the different tastes and purposes required to match in the form and use any other textile method, Here comes the problem of research, the revival and development of knitting as a handicraft that contributes to the preservation of our heritage of Egypt in a contemporary fashion suitable for the use of newly opened jobs for young artisans as small projects with low cost and economic feasibility. The aim of the research is to revive the hand knitting industry with products that are in line with the requirements of the modern era and compete in the international markets while preserving the Egyptian identity while contributing to opening up new fields of youth employment opportunities as a nucleus for small projects that generate economic returns on the individual and society. A qualitative study and practical experience has been carried out to produce some handicraft products in hand-knit fashion in a contemporary manner and to display these products to consumers in the local market